2016
DOI: 10.1016/j.jtho.2016.09.124
|View full text |Cite
|
Sign up to set email alerts
|

The IASLC Mesothelioma Staging Project: Proposals for the M Descriptors and for Revision of the TNM Stage Groupings in the Forthcoming (Eighth) Edition of the TNM Classification for Mesothelioma

Abstract: This first evidence-based revision of the TNM classification for MPM leads to substantial changes in the T and N components and the stage groupings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 8 publications
2
112
1
2
Order By: Relevance
“…In 2016, the International Association for the Study of Lung Cancer (IASLC) Staging Committee published proposals for the revisions of the T, N and M descriptors for the eighth edition of the TNM classification of MPM 11 . This was an international, multi-institutional cohort study.…”
Section: Section 4: Staging Systemsmentioning
confidence: 99%
“…In 2016, the International Association for the Study of Lung Cancer (IASLC) Staging Committee published proposals for the revisions of the T, N and M descriptors for the eighth edition of the TNM classification of MPM 11 . This was an international, multi-institutional cohort study.…”
Section: Section 4: Staging Systemsmentioning
confidence: 99%
“…In addition, sensitive and specific biomarkers for MPM are urgently needed for screening of asbestos-exposed subjects, since early diagnosed patients may benefit a better survival through a more effective multimodality therapy (surgery combined with radiotherapy and chemotherapy) (66,67). Nevertheless, biomarkers for routinely early diagnosis and screening are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…MM is mostly diagnosed at an advanced stage when it is poorly responsive to the current therapies and it was demonstrated that early diagnosis significantly improves overall survival (5,29,30). However, the currently available tissue and serological diagnostic biomarkers are characterized by relatively poor sensitivity and specificity preventing the use of reliable tools both for identification of individuals exposed to asbestos and other carcinogenic fibers and for early detection in patients who are developing MM (109).…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy and combination therapy have been widely investigated for the treatment of MM however, all therapeutic strategies failed to significantly benefit patients so far (25)(26)(27)(28). On the other hand, it has been shown that when patients are diagnosed and treated at an early stage (stage I) of MM, the overall median survival is significantly improved (29,30). Therefore, the relevance of early diagnosis of MM is very high for a better response to therapy.…”
Section: Review Articlementioning
confidence: 99%